A Convergence Result for Some Krylov–Tikhonov Methods in Hilbert Spaces. (26th April 2018) - Novati, P.
ABSTRACT: In this paper, we present a convergence result for some Krylov projection methods when applied to the Tikhonov minimization problem in its general form. In particular, we consider the method based on the Arnoldi algorithm and the one based on the Lanczos bidiagonalization process.